2018
DOI: 10.1021/acs.jpcb.8b06310
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Nanowire Sensors via High-Energy Single-Particle-Induced Linear Polymerization of 9,9′-Spirobi[9H-fluorene] Derivatives

Abstract: Nanostructures composed of conjugated polymers or π-conjugated molecules provide sensing platforms with large specific surface areas. One of the feasible approaches to accessing such nanostructured miniaturized sensors with ultrahigh sensitivity is to develop a network of organic nanowires with optical/electronic properties that can measure signals upon interacting with the analytes at their surfaces. In this work, organic nanowires with controlled number density and uniform length were fabricated by one-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…We previously reported that SBF frameworks were likely to be reacted upon irradiation of high LET charged particles and formed into clear and uniform nanowires by the STLiP process [16]. Halogenation of aromatic rings of SBF enhances the overall polymerization reactions mediated by free radicals remarkably due to DEA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that SBF frameworks were likely to be reacted upon irradiation of high LET charged particles and formed into clear and uniform nanowires by the STLiP process [16]. Halogenation of aromatic rings of SBF enhances the overall polymerization reactions mediated by free radicals remarkably due to DEA.…”
Section: Resultsmentioning
confidence: 99%
“…1). The key factor in the STLiP technique is to achieve gelation with high enough insolubility against successive wet development process with strong solvent for initial target molecules [15][16][17][18], and thus to trigger efficiently the initiation reactions and promote propagation reactions in a charged particle track.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates a transition percolation stage with a relatively wide range, i.e., 0.16 mg cm −2 m d 0.32 mg cm −2 , a distinctive feature of nano-particle percolation [17,18]. In this transition stage the main conduction mechanism switches from electron tunneling at m d =0.16 mg cm −2 to contact conductance at m d =0.32 mg cm −2 [17,18]. R changes rapidly with m d in the transition stage.…”
Section: Electric Percolation and Hysteresismentioning
confidence: 93%
“…Specifically, the electrical percolation threshold of AgNPs on the PDMS surface is found to be around m d =0.16 mg cm −2 as R decreases rapidly from 59 Ω to 1.04 Ω by nearly 60 times when m d grow from 0.16 mg cm −2 to 0.32 mg cm −2 by a factor of 2. This indicates a transition percolation stage with a relatively wide range, i.e., 0.16 mg cm −2 m d 0.32 mg cm −2 , a distinctive feature of nano-particle percolation [17,18]. In this transition stage the main conduction mechanism switches from electron tunneling at m d =0.16 mg cm −2 to contact conductance at m d =0.32 mg cm −2 [17,18].…”
Section: Electric Percolation and Hysteresismentioning
confidence: 93%
“…Further analyses from the mechanistic and quantitative aspects were performed by employing 9,9 -spirobi[9H-fluorene] (SBF) and its brominated derivatives [114]. Spin-coated films of SBF, 2-bromo-SBF (2Br-SBF), 4-bromo-SBF (4Br-SBF), 2,2 -dibromo-SBF (2,2 Br 2 -SBF), 2,7-dibromo-SBF (2,7Br 2 -SBF), 2,2 ,7,7 -tetrabromo-SBF (Br 4 -SBF), 2,2 -bi-9,9'-spirobi[9H-fluorene] (SBF 2 ), and 2,2 :7 ,2 -ter-9,9 -spirobi[9H-fluorene] (SBF 3 ) were irradiated with 350 MeV 129 Xe 26+ ions, and their nanowires were isolated after development with toluene.…”
Section: Single Particle Triggered Linear Polymerization (Stlip): Facmentioning
confidence: 99%